Raman investigation of structural photoinduced irreversible changes of Ga10Ge25S65 chalcogenide glasses - Messaddeq, S. H.; Li, M. Sui; Lezal, D.; Messaddeq, Y. [UNESP]; Ribeiro, S. J.L. [UNESP]; Oliveira, L. F.C.; Rollo, J. M.D.A. (My University, 2001)
The influence of time exposure, when exposed to above band gap light (3,52 eV) and annealing, on Ga10Ge25S65 glasses has been studied through their effects on the structure and optical properties. To evaluate the photostructural change infrared and Raman spectra for bulk Ga10Ge25S65 glasses have been measured before and after exposure. The Raman spectra are interpreted in terms of models in which the Ge atoms are fourfold coordinated and the S atoms are two fold coordinated. The observed changes in the spectral region of (S-S) stretching vibration (470-490 cm-1) is a direct evidence for the occurrence of important structural changes in local bonding configuration caused by optical irradiation. It is shown that the dominant photostrucural changes are chain formation tendency of the chalcogenide atoms under the laser irradiation rather than rings.
Keywords: Chalcogenide; GaGeS bulk glass; Photoexpansion; Raman spectra